Coordination Exercise for 10 Year Old Beginner Tennis Players - Gumilar Mulya; Resty Agustryani (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: There are many forms of training to improve the quality of physical condition of the tennis court athletes, one of which is coordination training. Thus, the author would like to try applying various forms of coordination exercises that are applied to children aged 10—11 years who participate in tennis clubs in the City of Tasikmalaya to support hand coordination. The aim of this research is to find out eye-hand coordination in elementary school students. The focus of this research is limited to the effectiveness of Coordination to support good physical condition in children. This research used experimental research methods. The population in this research were all 30 children who joined the tennis club in Tasikmalaya City. The sampling technique used is the total sampling technique. In order to get objective data, the author uses a measuring instrument in the form of a test that is eye-hand coordination test. Based on the results of this research and statistical calculations on the data obtained in this research, the authors can conclude that coordination exercises have a significant influence on improving eye-hand coordination especially for beginner tennis players of elementary school age.